The Influence Of Work-Life Balance And Motivation On Employee Performance: A Case Study At The Faculty Of Medicine, North Sumatera University, With Job Satisfaction As A Mediator - Margolang, Rizka Khairunnisa (Journal of International Conference Proceedings, 2024)
In the era of globalization and the industrial revolution 4.0, improving human resources quality becomes crucial in achieving organizational success. Human resource management (HRM) plays a crucial role as it significantly contributes to organizational goals. Each individual within the organization is a valuable investment, as their potential can be optimally utilized to achieve success. Therefore, HRM must be carried out carefully and effectively. Employee performance also plays a key role in the operational aspects of educational institutions and significantly influences organizational goals. Employee performance at the Faculty of Medicine, North Sumatera University, is a crucial factor in achieving academic organizational objectives. This study aims to identify factors influencing employee performance, namely Work-Life Balance, Motivation, Organizational Culture, and Job Satisfaction. The research method used is associative causal research with a quantitative approach. The research sample consists of 99 employees selected using total sampling method. Data were collected through interviews, documentary studies, and questionnaires. The analysis results indicate that Motivation has a significant positive  influence on Job Satisfaction, while Work motivation  has a significant positive influence. Work-Life Balance has a significant positive  influence on Employee Performance, but Work motivation  has a significant positive influence on Employee Performance. Additionally, Job Satisfaction has a significant positive influence on Employee Performance. Recommendations from this study include the management of the Faculty of Medicine, North Sumatera University, paying attention to employee Work-Life Balance and strengthening positive organizational culture. Providing incentives or rewards to employees who achieve high job satisfaction levels is also suggested to enhance overall performance.Keywords: Work-Life Balance, Motivation, Employee Performance, Job Satisfaction